2002
DOI: 10.1152/physiolgenomics.00112.2001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of zebrafish NFE2

Abstract: Vertebrate hematopoiesis is regulated by distinct cell-specific transcription factors such as GATA-1 and SCL. Mammalian p45-NFE2 was characterized for its ability to bind the hypersensitive sites of the globin locus control region. NFE2 is a member of a cap'n'collar (CNC) and basic zipper (BZIP) superfamily that regulates gene transcription. It has been implicated in diverse processes such as globin gene expression, oxidative stress, and platelet lineage differentiation. Here, we have isolated the zebrafish or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…Single zebrafish homologs of NF-E2 and NRF2 have been described previously (10,38). In examining the zebrafish genome and predicted protein set, we identified two predicted zebrafish homologs of mammalian NRF1, a predicted NRF3 ortholog, and a second predicted NRF2 form.…”
Section: Identification Of Nf-e2-related Factors In Zebrafish-mentioning
confidence: 99%
“…Single zebrafish homologs of NF-E2 and NRF2 have been described previously (10,38). In examining the zebrafish genome and predicted protein set, we identified two predicted zebrafish homologs of mammalian NRF1, a predicted NRF3 ortholog, and a second predicted NRF2 form.…”
Section: Identification Of Nf-e2-related Factors In Zebrafish-mentioning
confidence: 99%
“…Several other family members, such as BTB-CNC, allogeneic Bach1 and Bach2 (Oyake et al 1996), Nrf3 (Kobayashi et al 1999), and p45-NFE2 (Pratt et al 2002) have since been identified. Nrf2 is a leucine zipper/CNC protein, a polypeptide with a molecular weight of 66 kDa, and it is widely expressed in organs with hyperoxia consumption, such as the muscle, heart, vasculature, liver, kidney, brain, lung, skin, and digestive tract.…”
Section: Introductionmentioning
confidence: 99%
“…However, because MafK lacks a transactivation domain, it regulates transcription through interaction with the cap‘n’collar (CNC) bZIP proteins, including Nrf2 and Bach1 (Toki et al, 2005; Igarashi and Sun, 2006; Blank, 2008). The Nrf2-MafK heterodimer serves as an activator (Pratt et al, 2002; Kobayashi and Yamamoto, 2006), whereas the Bach1-MafK heterodimer functions as a repressor because Bach1 harbors a transcription-repressing BTB/POZ domain (Toki et al, 2005; Igarashi and Sun, 2006; Blank, 2008). Moreover, heme binds to Bach1 through its cysteine-proline (CP) dipeptide-containing heme regulatory motifs (HRMs) (Fig.…”
Section: Introductionmentioning
confidence: 99%